2002
DOI: 10.1046/j.0022-202x.2001.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative Electric Potential Induces Alteration of Ion Gradient and Lamellar Body Secretion in the Epidermis, and Accelerates Skin Barrier Recovery After Barrier Disruption

Abstract: Previous reports suggested that ion gradients of ions such as calcium and magnesium in the epidermis play a crucial part in skin barrier homeostasis. We hypothesized that external electric potential affects the ionic gradient and skin barrier homeostasis. We demonstrated here that application of a negative electric potential (0.50 V) on hairless mice skin accelerated the barrier recovery approximately 60.7% of the original level within 1 h compared with control (37.5%) after barrier disruption by acetone treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 43 publications
1
37
1
Order By: Relevance
“…It has been also reported that barrier disruption, hallmark of AD, was related to the decrease of calcium, magnesium, potassium, and zinc in in vitro and animal studies (Denda et al, 2000;Denda and Kumazawa, 2002;Makiura et al, 2004), although these associations are not clear in human studies (Tricon et al, 2006). Like zinc shown in Table 2, when we analyzed our data regarding the intakes of calcium and potassium, there was no statistically significant association between these nutrients and AD in this study (data not shown).…”
Section: Discussionmentioning
confidence: 41%
“…It has been also reported that barrier disruption, hallmark of AD, was related to the decrease of calcium, magnesium, potassium, and zinc in in vitro and animal studies (Denda et al, 2000;Denda and Kumazawa, 2002;Makiura et al, 2004), although these associations are not clear in human studies (Tricon et al, 2006). Like zinc shown in Table 2, when we analyzed our data regarding the intakes of calcium and potassium, there was no statistically significant association between these nutrients and AD in this study (data not shown).…”
Section: Discussionmentioning
confidence: 41%
“…Moreover, in this study, we loaded the electric potential on untreated ex vivo skin, while in our previous mouse study, we had loaded the potential after barrier disruption. Our earlier study suggested that external potential influenced lamellar body secretion during barrier recovery after disruption (1). On the other hand, the present findings suggest that exocytosis of lamellar bodies and fusion of secreted lipids might be regulated by the electro-physiological condition of the epidermis even in normal skin.…”
Section: Resultscontrasting
confidence: 37%
“…Moreover, the application of negative electric potential after barrier disruption increased the calcium ion gradient at the uppermost nucleated layer of the epidermis (1). In this study, we observed calcium ion gradation in the epidermis of control skin and potential-loaded skin by means of two-photon microscopy.…”
Section: Letter To the Editormentioning
confidence: 66%
See 1 more Smart Citation
“…In a preliminary study, we have previously reported a mineral imbalance in AEDS patients (Hanifin & Rajka, 1980;Kimata et al, 2002). Moreover, skin barrier recovery is influenced by the electric charge of minerals in the epithelium (Edelberg, 1977;Denda et al, 2000;Denda & Kumazawa, 2002). Mg deficiency results in AEDS-like symptoms in hairless rats (Neckermann et al, 2000a, b;Makiura et al, 2004).…”
Section: Discussionmentioning
confidence: 99%